Cultural roots of Russian sophiology - Donskikh, Oleg A. (Sophia, 1995)
The development of Russian culture predetermined three propensities which form the intellectual framework of Russian national philosophy—historicism, mysticism and aestheticism. The most significant conceptions of Russian philosophy, united by the idea and image of Sophia, are defined by this framework., There is no contradiction in Russian philosophy between rational and mystical modes of thought because they are complementary in this tradition. It is, however, necessary to redefine the conception of rationality., I would like to finish with Solovyov's words: “The idea of a nation is not what it thinks of itself in time, but what God thinks of it in eternity”.